High-performance bi-based heterostructure electrocatalyst and preparation method and application thereof

By electrochemically reconstructing and defect-tuning the BiVO4 precursor, a Bi2/BiVO4-x heterostructure is formed, which solves the problem of low catalyst efficiency in CO2 reduction reaction and achieves efficient formate selective conversion and improved battery performance.

CN120138681BActive Publication Date: 2025-12-05ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510400903.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-12-05
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

Existing CO2 reduction catalysts exhibit low efficiency and poor selectivity when converting CO2 to formate, and the high activation energy of the competitive hydrogen evolution reaction leads to poor catalytic efficiency.

Method used

By electrochemically reconstructing and defect-tuning the BiVO4 precursor, a Bi2/BiVO4-x heterostructure is formed, and the interfacial electron transfer kinetics and catalytic active sites are adjusted to prepare a high-performance Bi-based heterostructure electrocatalyst.

Benefits of technology

It achieves highly efficient selective conversion of formate, improves the overall efficiency of CO2 reduction reaction, and exhibits excellent battery performance and Faraday efficiency in reversible zinc-carbon dioxide batteries and co-electrolysis systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120138681B_ABST
    Figure CN120138681B_ABST
Patent Text Reader

Abstract

This invention provides a high-performance Bi-based heterostructure electrocatalyst, its preparation method, and its application. The molecular formula of the electrocatalyst is Bi2 / BiVO2. 4‑x The electrocatalyst exhibits a heterogeneous structure with oxygen vacancies. The lattice spacing of the nanoparticles is 0.395 nm, corresponding to the (003) plane of metallic Bi. The lattice stripe spacing of the support for the electrocatalyst is 0.467 nm, corresponding to BiVO4. 4‑x The (011) side. This invention prepares Bi2 / BiVO with a heterostructure via a hydrothermal reaction-heat treatment-electrochemical reconstruction method. 4‑x The electrocatalyst enhances the activity and selectivity of electrocatalytic carbon dioxide reduction (CO2RR) to formate through strong interfacial interactions and exposure of abundant catalytic sites. It exhibits a formate Faradaic efficiency exceeding 90% over a wide potential window and demonstrates good stability. Furthermore, Bi2 / BiVO2... 4‑x The electrocatalyst exhibits excellent battery power density and high total formate Faraday efficiency in both reversible zinc-carbon dioxide batteries (Zn-CO2) and formate co-electrolysis systems.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of nanomaterials and electrocatalysis, and particularly to a high-performance Bi-based heterostructure electrocatalyst and a preparation method and application thereof. BACKGROUND

[0002] The continuous combustion of fossil fuels has led to a significant increase in the concentration of carbon dioxide (CO2) in the atmosphere, which has seriously affected global climate, environmental stability and human health. In order to address this challenge, the development of electrocatalytic CO2 reduction reaction (CO2RR) technology has become a very promising strategy, which can reduce the accumulation of CO2 while converting it into value-added chemicals such as carbon monoxide, formate, hydrocarbons and alcohols. Among them, formate (HCOO-) has attracted more and more attention due to its wide market demand and wide application in rubber, textiles, leather processing, pesticides and pharmaceuticals. In addition, as a hydrogen storage and transportation medium, formate plays a crucial role in direct formic acid fuel cells due to its high energy density and environmental compatibility. Although people are increasingly interested in the conversion of CO2RR to formate, the high intrinsic activation energy required for CO2 reduction and the competing hydrogen evolution reaction (HER) often leads to low catalytic efficiency and poor product selectivity. Therefore, the development and optimization of advanced electrocatalysts that can inhibit HER and enhance formate selectivity are crucial for improving the overall efficiency of CO2RR. SUMMARY

[0003] (I) Technical problems solved

[0004] In view of the deficiencies of the prior art, the present application provides a high-performance Bi-based heterostructure electrocatalyst and a preparation method and application thereof. By electrochemically restructuring and defect regulating the BiVO4 precursor, the Bi2 / BiVO4 coupled heterostructure is adjusted to improve the interface electron transfer dynamics and rich catalytic active sites, and a high-activity electrocatalyst is constructed to solve the problems raised in the above background. 4-x The present application provides a high-performance Bi-based heterostructure electrocatalyst and a preparation method and application thereof.

[0005] (II) Technical solutions

[0006] To achieve the above object, the present application is implemented by the following technical solutions:

[0007] According to a first aspect of the present application, a high-performance Bi-based heterostructure electrocatalyst is provided, the molecular formula of the electrocatalyst is Bi2 / BiVO4, the electrocatalyst has a heterostructure and oxygen defects, the lattice spacing of the nanoparticles of the electrocatalyst is 0.395 nm, corresponding to the (003) plane of metallic Bi, and the lattice stripe spacing of the carrier of the electrocatalyst is 0.467 nm, corresponding to the (011) plane of BiVO4. 4-x 4-x According to a first aspect of the present application, a high-performance Bi-based heterostructure electrocatalyst is provided, the molecular formula of the electrocatalyst is Bi2 / BiVO4, the electrocatalyst has a heterostructure and oxygen defects, the lattice spacing of the nanoparticles of the electrocatalyst is 0.395 nm, corresponding to the (003) plane of metallic Bi, and the lattice stripe spacing of the carrier of the electrocatalyst is 0.467 nm, corresponding to the (011) plane of BiVO4.​

[0008] Preferably, the electrocatalyst has a multi-stage sheet structure with a size of 50-200 nm.

[0009] According to a second aspect of the application, a preparation method of a high-performance Bi-based heterostructure electrocatalyst is provided, comprising the following steps:

[0010] (1) adding bismuth nitrate into a nitric acid solution, stirring uniformly to obtain a transparent solution A; adding ammonium metavanadate into a sodium hydroxide solution, and ultrasonic treatment to obtain a uniform solution B;

[0011] (2) mixing the transparent solution A and the uniform solution B uniformly, continuously stirring, transferring to a polytetrafluoroethylene-lined high-pressure reactor for hydrothermal reaction, naturally cooling to room temperature, centrifuging to collect the precipitate, sequentially washing with deionized water and ethanol, and vacuum drying to obtain a BiVO4 precursor powder;

[0012] (3) placing the BiVO4 precursor powder in a tube furnace, and performing heat treatment under a mixed gas atmosphere containing hydrogen and nitrogen, and taking out the sample after the furnace is cooled to room temperature;

[0013] (4) performing in-situ electro-reduction on the sample to obtain the electrocatalyst.

[0014] Preferably, in step (1), the molar amount of bismuth nitrate in the transparent solution A is 4-6 mmol, and the concentration of the nitric acid solution is 3-5 M;

[0015] the molar amount of ammonium metavanadate in the uniform solution B is 4-6 mmol, and the concentration of the sodium hydroxide solution is 1-3 M.

[0016] Further preferably, the molar amount of bismuth nitrate in the transparent solution A is 5 mmol, and the concentration of the nitric acid solution is 4 M;

[0017] the molar amount of ammonium metavanadate in the uniform solution B is 5 mmol, and the concentration of the sodium hydroxide solution is 2 M.

[0018] Preferably, in step (2), the continuously stirring time is 10-40 min;

[0019] the temperature of the hydrothermal reaction is 180-220℃, and the time of the hydrothermal reaction is 1-2 h.

[0020] Further preferably, in step (2), the continuously stirring time is 30 min;

[0021] the temperature of the hydrothermal reaction is 200℃, and the time of the hydrothermal reaction is 1.5 h.

[0022] Preferably, in step (3), the volume ratio of hydrogen to nitrogen in the mixed gas atmosphere containing hydrogen and nitrogen is 1:4.

[0023] The temperature of the heat treatment is 100-300℃, and the time is 1-3h.

[0024] Further preferably, the temperature of the heat treatment is 200℃, and the time is 2h.

[0025] Preferably, in step (4), the voltage of the in-situ electro-reduction is -0.7 to -0.9V vs. RHE, and the time of the in-situ electro-reduction is 20-40min.

[0026] Further preferably, in step (4), the voltage of the in-situ electro-reduction is -0.8V vs. RHE, and the time of the in-situ electro-reduction is 30min.

[0027] According to a third aspect of the present application, there is provided a use of the high-performance Bi-based heterostructure electrocatalyst or the high-performance Bi-based heterostructure electrocatalyst obtained by the above preparation method in a carbon dioxide electro-reduction reaction.

[0028] Preferably, in a flow-type electrolytic cell, the Bi-based heterostructure electrocatalyst has a formate Faraday efficiency (FE) ≥90% in a potential range of -0.5 to -1.0V (vs. RHE).

[0029] According to a fourth aspect of the present application, there is provided a use of the high-performance Bi-based heterostructure electrocatalyst or the high-performance Bi-based heterostructure electrocatalyst obtained by the above preparation method in a reversible zinc-carbon dioxide battery.

[0030] Specifically, the high-performance Bi-based heterostructure electrocatalyst is used as a cathode, a zinc foil is used as an anode, a cathode electrolyte is 0.5M potassium bicarbonate, an anode electrolyte is a mixture of 6M potassium hydroxide and 0.2M zinc acetate, and the maximum power density of the battery reaches 5mW / cm 2 .

[0031] According to a fifth aspect of the present application, there is provided a use of the high-performance Bi-based heterostructure electrocatalyst or the high-performance Bi-based heterostructure electrocatalyst obtained by the above preparation method in a carbon dioxide reduction coupled with glycerol oxidation (CO2RR||GOR) co-electrolysis system.

[0032] Specifically, Bi2 / BiVO 4-x ||Co2P@MoO x electrode combination, the total Faraday efficiency of formate can reach 189.5% at 0.8V.

[0033] (III) Beneficial Effects

[0034] This invention provides a high-performance Bi-based heterostructure electrocatalyst, its preparation method, and its application. It possesses the following beneficial effects:

[0035] (1) This scheme provides a method for preparing a high-performance Bi-based heterostructure electrocatalyst, which involves calcining the BiVO4 precursor in a reducing atmosphere to regulate its surface oxygen defects, and then electrochemically reconstructing it in situ to prepare Bi2 / BiVO4. 4-x In heterogeneous catalysts, the formation of oxygen vacancies and the construction of heterogeneous interfaces are beneficial to the regulation of the electronic structure and active surface area of ​​the material, giving it more sites for adsorption of active species and rapid conversion reaction kinetics, thereby achieving excellent formate selective conversion performance.

[0036] (2) The high-performance Bi-based heterostructure electrocatalyst provided in this scheme exhibits excellent battery performance in rechargeable Zn-CO2 batteries and has important application value in energy storage and carbon dioxide resource utilization.

[0037] (3) The high-performance Bi-based heterostructure electrocatalyst provided in this scheme exhibits extremely high Faraday efficiency and cycle stability in the membrane electrode co-electrolysis production system of formate, proving its great application potential in the actual production of value-added formate. Attached Figure Description

[0038] Figure 1 This is a schematic diagram illustrating the synthesis of a high-performance Bi-based heterostructure electrocatalyst according to the present invention.

[0039] Figure 2 X-ray diffraction patterns of the electrocatalysts prepared in Example 1 and Comparative Examples 1 to 3 of this invention;

[0040] Figure 3 The electrocatalyst Bi2 / BiVO prepared in Example 1 of this invention 4-x Transmission electron microscopy (TEM) images, where (a) is a TEM image and (b) is a HRTEM image;

[0041] Figure 4 The electrocatalyst Bi2 / BiVO prepared in Example 1 of this invention 4-x The catalysts Bi / BiVO prepared in Comparative Examples 1 to 3 respectively 4-x Bi1 / BiVO 4-x Bi3 / BiVO 4-x LSV curves obtained by flow cell testing in CO2-saturated electrolyte;

[0042] Figure 5 The electrocatalyst Bi2 / BiVO prepared in Example 1 of this invention 4-x The catalysts Bi / BiVO prepared in Comparative Examples 1 to 3 respectively4-x Bi1 / BiVO 4-x Bi3 / BiVO 4-x Faraday efficiency plot of formate products in a flow cell;

[0043] Figure 6 The electrocatalyst Bi2 / BiVO prepared in Example 1 of this invention 4-x Stability test results in the flow cell;

[0044] Figure 7 The electrocatalyst Bi2 / BiVO prepared in Example 1 of this invention 4-x Discharge polarization curves and power density curves in Zn-CO2 batteries;

[0045] Figure 8 The electrocatalyst Bi2 / BiVO prepared in Example 1 of this invention 4-x LSV curves in a carbon dioxide reduction coupled with glycerol oxidation (CO2RR||GOR) co-electrolysis system;

[0046] Figure 9 The electrocatalyst Bi2 / BiVO prepared in Example 1 of this invention 4-x Formate Faraday efficiency at different voltages in a carbon dioxide reduction coupled with glycerol oxidation (CO2RR||GOR) co-electrolysis system;

[0047] Figure 10 The electrocatalyst Bi2 / BiVO prepared in Example 1 of this invention 4-x Stability test diagram of carbon dioxide reduction coupled with glycerol oxidation (CO2RR||GOR) co-electrolysis system. Detailed Implementation

[0048] To better illustrate the content of this invention, the following description is provided in conjunction with specific embodiments.

[0049] Example 1

[0050] A method for preparing a high-performance Bi-based heterostructure electrocatalyst, the synthesis process is as follows: Figure 1 As shown, it includes the following steps:

[0051] Step 1: Dissolve 5 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H3O) in 10 mL of 4 M nitric acid (HNO3) and stir magnetically until completely dissolved to obtain a transparent solution A; dissolve 5 mmol of ammonium metavanadate (NH4VO3) in 10 mL of 2 M sodium hydroxide (NaOH) solution and sonicate for 10 min to form a homogeneous solution B;

[0052] Step 2: Mix the transparent solution A and the homogeneous solution B evenly, stir continuously for 30 min, transfer to a 50 mL high-pressure reactor lined with polytetrafluoroethylene, carry out hydrothermal reaction at 200 °C for 1.5 h, cool naturally to room temperature, collect the precipitate by centrifugation, wash with deionized water and ethanol three times in sequence, and vacuum dry at 60 °C for 12 h to obtain BiVO4 precursor powder.

[0053] Step 3: Place the BiVO4 precursor powder in a tube furnace and heat it at 5°C for 1 minute under an H2 / N2 mixed gas atmosphere (volume ratio 1:4). -1 The sample was heat-treated at 200℃ for 2 hours at a heating rate of 200℃. After the furnace temperature dropped to room temperature, the sample was taken out and stored in a dry container for later use.

[0054] Step four: The collected sample was subjected to in-situ electroreduction at -0.8V vs. RHE for 30 min to obtain the electrocatalyst Bi2 / BiVO2. 4-x .

[0055] Example 2

[0056] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the molar amounts of bismuth nitrate pentahydrate (Bi(NO3)3·5H3O) and ammonium metavanadate (NH4VO3) are 4 mmol and 4 mmol, respectively.

[0057] Example 3

[0058] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the molar amounts of bismuth nitrate pentahydrate (Bi(NO3)3·5H3O) and ammonium metavanadate (NH4VO3) are 6 mmol and 6 mmol, respectively.

[0059] Example 4

[0060] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is described, which is the same as the preparation method in Example 1, except that the concentration of the nitric acid (HNO3) solution is 3M.

[0061] Example 5

[0062] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is described, which is the same as the method in Example 1, except that the concentration of the nitric acid (HNO3) solution is 5M.

[0063] Example 6

[0064] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided, which is the same as the preparation method in Example 1, except that the concentration of the sodium hydroxide (NaOH) solution is 1M.

[0065] Example 7

[0066] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is described, which is the same as the preparation method in Example 1, except that the concentration of the sodium hydroxide (NaOH) solution is 3M.

[0067] Example 8

[0068] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the stirring time is 10 min during the mixing of transparent solution A and homogeneous solution B.

[0069] Example 9

[0070] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the stirring time is 20 min during the mixing of transparent solution A and homogeneous solution B.

[0071] Example 10

[0072] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the stirring time is 40 min during the mixing of transparent solution A and homogeneous solution B.

[0073] Example 11

[0074] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the hydrothermal reaction temperature is 180°C.

[0075] Example 12

[0076] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the hydrothermal reaction temperature is 220°C.

[0077] Example 13

[0078] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the hydrothermal reaction time is 1 hour.

[0079] Example 14

[0080] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the hydrothermal reaction time is 2 hours.

[0081] Example 15

[0082] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the heat treatment time is 1 hour.

[0083] Example 16

[0084] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the heat treatment time is 3 hours.

[0085] Example 17

[0086] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is described, which is the same as the method in Example 1, except that the voltage for in-situ electroreduction is -0.7V vs. RHE.

[0087] Example 18

[0088] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is described, which is the same as the method in Example 1, except that the voltage for in-situ electroreduction is -0.9V vs. RHE.

[0089] Example 19

[0090] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the in-situ electroreduction time is 20 min.

[0091] Example 20

[0092] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is provided. The preparation method is the same as that in Example 1, except that the in-situ electroreduction time is 40 min.

[0093] Comparative Example 1

[0094] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is disclosed. The preparation method is the same as that in Example 1, except that the BiVO4 precursor powder is not heat-treated, but directly electroreduced in situ at -0.8V vs. RHE for 30 min to obtain Bi / BiVO4. 4-x .

[0095] Comparative Example 2

[0096] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is disclosed. The preparation method is the same as that in Example 1, except that the heat treatment temperature is controlled at 100°C instead of 200°C, followed by in-situ electroreduction at -0.8V vs. RHE for 30 min to obtain Bi1 / BiVO. 4-x .

[0097] Comparative Example 3

[0098] A method for preparing a high-performance Bi-based heterostructure electrocatalyst is disclosed. The preparation method is the same as that in Example 1, except that the heat treatment temperature is controlled at 300℃ instead of 200℃, followed by in-situ electroreduction at -0.8V vs. RHE for 30 min to obtain Bi3 / BiVO4. 4-x .

[0099] Performance testing

[0100] XRD analysis was performed on the electrocatalysts prepared in Example 1 and Comparative Examples 1-3, such as... Figure 2 As shown, the XRD patterns of the four catalysts all show diffraction peaks of metallic Bi (PDF#85-1329) and diffraction peaks of BiVO4 (PDF#75-2480), indicating that the catalysts are a mixture of metallic Bi and BiVO4.

[0101] Bi2 / BiVO prepared in Example 1 4-x Electrocatalysts were analyzed by TEM, such as Figure 3 As shown, according to Figure 3 As shown in Figures a and b, the HRTEM images reveal two distinct lattice patterns. The lattice spacing of the nanoparticles is 0.395 nm, corresponding to the (003) plane of metallic Bi, while the lattice spacing of the support is 0.467 nm, corresponding to BiVO₄. 4-x The (011) facet indicates Bi2 / BiVO. 4-x A well-coupled heterogeneous interface was formed.

[0102] The electrocatalysts prepared in Example 1 and Comparative Examples 1-3 were tested in a flow electrolyzer. Figure 4 As shown, the electrolyte is a 1M potassium hydroxide solution, Bi2 / BiVO2. 4-x The catalyst exhibits higher current density and smaller onset potential, indicating that Bi2 / BiVO 4-x It exhibits optimal CO2RR activity.

[0103] The electrocatalysts prepared in Example 1 and Comparative Examples 1-3 were tested in a flow electrolyzer. Figure 5As shown, in the potential range of -0.5V to -1.0V (vs. RHE), Bi2 / BiVO 4-x It consistently exhibits the highest formate Faradaic efficiency (FE) at different potentials. It achieves the maximum formate FE of 96.8% at -0.8V (vs. RHE), which is superior to the electrocatalysts prepared in Comparative Examples 1 to 3.

[0104] To evaluate the Bi2 / BiVO 4-x The electrocatalyst's long-term cycling stability and ability to continuously produce formate were tested. Figure 6 Bi2 / BiVO prepared in Example 1 4-x The electrocatalyst was subjected to continuous CO2RR electrolysis tests using a flow cell. Chronoamperometry (CFC) curves and the Faradaic efficiency of the formate electrolysis product were obtained after 100 hours of electrolysis at a constant potential of -0.8 V vs. RHE. The test results indicate that the Bi2 / BiVO2 prepared by this method... 4-x The electrocatalyst exhibits excellent stability in the continuous production of formate.

[0105] Figure 7 It is the Bi2 / BiVO synthesized in Example 1 4-x The performance of electrocatalysts in rechargeable Zn-CO2 batteries, such as Figure 7 As shown, the assembled Zn-CO2 battery exhibits excellent charge / discharge performance, and at 6 mA / cm², it achieves this. 2 Peak power can reach 5mW / cm 2 .

[0106] Figure 8 For Co2P@MoO x The sample was used as an anode catalyst, in conjunction with the Bi2 / BiVO2 prepared in Example 1 of this invention. 4-x An electrocatalyst was used as the cathode in a co-electrolysis system, in which the cathode electrolyte was 1M potassium hydroxide and the anode electrolyte was 1M potassium hydroxide + 0.1M glycerol. The results showed that replacing OER with GOR could achieve a lower voltage, indicating its improved energy efficiency.

[0107] Figure 9 For Co2P@MoO x The sample was used as an anode catalyst, in conjunction with the Bi2 / BiVO2 prepared in Example 1 of this invention. 4-x The catalyst was used as the cathode in the co-electrolysis system. The results showed that the CO2RR||GOR system achieved a total Faradaic efficiency (FE) of over 150% formate production in the voltage range of 0.5 to 1.0 V. At 0.8 V, the total FE for formate production by the two electrodes reached approximately 189.5%, with the cathode CO2RR contributing 94.5% and the anode GOR contributing 95%.

[0108] Figure 10 For Co2P@MoO x The sample was used as an anode catalyst, in conjunction with the Bi2 / BiVO2 prepared in Example 1 of this invention. 4-x The catalyst was used as the cathode in the co-electrolysis system. The results showed that the CO2RR||GOR electrolyzer exhibited excellent cycle stability, continuously producing formate for more than 15 hours without any significant performance degradation, demonstrating its good application potential.

[0109] Based on the above performance tests, it can be seen that the high-performance Bi-based heterostructure electrocatalyst, its preparation method, and its application provided by this invention, along with the electrochemical reconstruction and defect engineering strategy for a BiVO4 precatalyst prepared by the synthesis method provided by this invention, can adjust the Bi2 / BiVO4 ratio. 4-x The coupled heterostructure endows it with improved interfacial electron transfer kinetics and abundant catalytic active sites, thereby achieving efficient formate formation. Specifically, the optimized Bi2 / BiVO 4-x The highest Faradaic efficiency (FE) (96.8% at -0.8V vs. RHE) and high current density were achieved formate. When Bi₂ / BiVO 4-x When the catalyst is applied to a Zn-CO2 battery, it achieves a current of 6 mA / cm². 2 It can provide 5mW / cm 2 Peak power. Furthermore, in the formate co-electrolysis system, the electrolyzer achieved extremely high formate FE (189.5% at 0.8V) with excellent stability.

[0110] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A high performance Bi-based heterostructured electrocatalyst, characterized in that: The molecular formula of the electrocatalyst is Bi2 / BiVO 4-x , is a heterostructure and has oxygen defects, the lattice spacing of the nanoparticles of the electrocatalyst is 0.395 nm, corresponding to the (003) plane of metal Bi, and the lattice stripe spacing of the carrier of the electrocatalyst is 0.467 nm, corresponding to the (011) plane of BiVO 4-x .

2. The high performance Bi-based heterostructured electrocatalyst of claim 1, wherein: The electrocatalyst has a multi-stage sheet structure with a size of 50-200 nm.

3. A method for preparing the high performance Bi-based heterostructure electrocatalyst according to claim 1 or 2, characterized in that: The method comprises the following steps: (1) adding bismuth nitrate into a nitric acid solution and stirring to obtain a transparent solution A; adding ammonium metavanadate into a sodium hydroxide solution and ultrasonic treating to obtain a uniform solution B; (2) mixing the transparent solution A and the uniform solution B uniformly, continuously stirring, transferring into a high-pressure reaction kettle with a polytetrafluoroethylene liner to perform a hydrothermal reaction, naturally cooling to room temperature, centrifugally collecting a precipitate, sequentially cleaning with deionized water and ethanol, and vacuum drying to obtain a BiVO4 precursor powder; (3) placing the BiVO4 precursor powder in a tube furnace, performing a heat treatment under a mixed gas atmosphere containing hydrogen and nitrogen, and taking out the sample after the furnace is cooled to room temperature; (4) performing in-situ electro-reduction on the sample to obtain the electrocatalyst.

4. The method according to claim 3, wherein the method is characterized by: In step (1), the molar amount of bismuth nitrate in the transparent solution A is 4-6 mmol, and the concentration of the nitric acid solution is 3-5 M. In the uniform solution B, the molar amount of ammonium metavanadate is 4-6 mmol, and the concentration of the sodium hydroxide solution is 1-3 M.

5. The method according to claim 3, wherein the method is characterized by: In step (2), the continuously stirring time is 10-40 min. The hydrothermal reaction temperature is 180-220 ℃, and the hydrothermal reaction time is 1-2 h.

6. The method according to claim 3, wherein the method is characterized by: In step (3), in the mixed gas atmosphere containing hydrogen and nitrogen, the volume ratio of hydrogen to nitrogen is 1:

4.

7. The method according to claim 3, wherein the method is characterized by: In step (4), the in-situ electro-reduction voltage is -0.7 to -0.9 V vs. RHE, and the in-situ electro-reduction time is 20-40 min.

8. Use of the high-performance Bi-based heterostructure electrocatalyst of claim 1 or 2 or the high-performance Bi-based heterostructure electrocatalyst obtained by the preparation method of any one of claims 3-7 in a carbon dioxide electro-reduction reaction.

9. Use of the high-performance Bi-based heterostructure electrocatalyst of claim 1 or 2 or the high-performance Bi-based heterostructure electrocatalyst obtained by the preparation method of any one of claims 3-7 in a reversible zinc-carbon dioxide battery.

10. Use of the high-performance Bi-based heterostructure electrocatalyst of claim 1 or 2 or the high-performance Bi-based heterostructure electrocatalyst obtained by the preparation method of any one of claims 3-7 in a carbon dioxide reduction coupled with glycerol oxidation (CO2RR||GOR) co-electrolysis system.